Pengaruh Harga Tiket dan Atraksi Wisata Terhadap Kepuasan Wisatawan Situgunung Suspension Bridge Sukabumi - Tesa Amellia; Umban Adi Jaya (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2021)
The purpose of this study was to determine the effect of tourist ticket prices and tourist attraction on tourist satisfaction at the Situgunung Sukabumi Suspension Bridge. The method used in this survey is a quantitative descriptive survey method, where questionnaires are distributed to 100 samples using the Objective Sampling method based on Situgunung tourism. The results of this study indicate that the Adjusted R-squared value is 71.8% which indicates that tourist satisfaction is positively and significantly influenced by ticket prices and tourist attractions with the regression equation Y = 9.828 + 0.433X1 + 1.157X2. Simultaneous analysis results show that ticket prices and tourist attractions have an effect on tourist satisfaction. The t-test shows that there is a partial effect between ticket prices and tourist attraction for tourist satisfaction.